Pymes, competencias laborales y TIC: Competitividad, productividad e innovación organizacional (2019)
This book takes as its main object of study small and medium enterprises (SMEs), from their competitive, productive, and organizational innovation possibilities. This leads us to seek to understand what are the specific needs of this type of companies to be able to face the current market conditions and how they could solve them. This is how it is necessary to understand how the emergence and use of information and communication technologies (ICT) can influence the improvement of different management and production processes within SMEs. But ICT can not only contribute to the improvement of its internal functioning; They are also tools that have proven to be very effective in the promotion, dissemination, and distribution of products and services. Thus, information technologies must be seen as a factor of productivity and competitiveness that, well-focused, can achieve effective positioning. From this derives the need to identify, for SMEs, the labor competencies that must be sought and promoted in their employees, to ensure the success of their objectives, based on their perspectives and possibilities of organizational innovation from a configurational approach. In other words, the idea is to be able to understand how, based on the understanding of their potential, projected and optimized through the use of ICT, SMEs can build a knowledge of themselves that allows them to generate innovative differentiators that ensure their competitiveness. SMEs, job skills, and ICT want to show that small and medium enterprises can and should be productive and competitive in the knowledge society. And this is achieved thanks to generating value, originality, creativity, and innovation, which, in turn, must function as the lever and engine of the economic and social development of the nation.